2020
DOI: 10.1101/2020.10.20.346577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Droplet printing reveals the importance of micron-scale structure for bacterial ecology

Abstract: Bacteria often live in diverse communities where the spatial arrangement of strains and species is considered critical for their ecology, including whether strains can coexist, which are ecologically dominant, and how productive they are as a community. However, a test of the importance of spatial structure requires manipulation at the fine scales at which this structure naturally occurs. Here we develop a droplet-based printing method to arrange different bacterial genotypes across a sub-millimetre array. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…However, when the two wild type strains competed against each other, KT2442 was eliminated, presumably because it was killed before it could fire its T6SS. In accordance with a recent report 81 , we observed that on agar plates dead cells created a barrier that prevented further killing. This was not observed when the biofilms were grown in flow cells, as dead KT2442 cells detached from the glass substratum and were removed by the shear forces of the nutrient flow.…”
Section: Discussionsupporting
confidence: 93%
“…However, when the two wild type strains competed against each other, KT2442 was eliminated, presumably because it was killed before it could fire its T6SS. In accordance with a recent report 81 , we observed that on agar plates dead cells created a barrier that prevented further killing. This was not observed when the biofilms were grown in flow cells, as dead KT2442 cells detached from the glass substratum and were removed by the shear forces of the nutrient flow.…”
Section: Discussionsupporting
confidence: 93%
“…Bacterial biofilms often experience steep antibiotic gradients when they are treated because the high cell density within these communities both attenuates diffusion and removes compounds from circulation (1)(2)(3). In addition, bacteria commonly live alongside other strains and species that themselves release antimicrobials that diffuse and can again generate chemical gradients (4)(5)(6). In order to cope with life under these conditions, bacteria have evolved a wide variety of physiological responses that detect and respond to toxic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For example, microbiologists have long reported the existence of (sometimes annoying (77)) “satellite” colonies (78), drug-sensitive populations that appear near enzyme-producing resistant colonies on agar plates, suggesting that resistance can be cooperative on scales of millimeters or more. Similarly long-range effects have been recently measured for oxygen gradients in biofilms (79), yet metabolic gradients have been shown to be relatively short-ranged (80), and droplet-based printing techniques have shown that specific microscale structure determines dynamics in interacting colicin-producing strains (81). In systems where intercellular interactions are primarily short-range–with resistance driven by intracellular drug degradation, for example (14)–recent work shows that additional physiological mechanisms, such as persistence, might be needed to drive cooperative resistance (18).…”
Section: Introductionmentioning
confidence: 89%